Neuroethics, Painience, and Neurocentric Criteria for the Moral Treatment of Animals - Loveless, Sherry E. (Cambridge quarterly of healthcare ethics, 2014)
Neuroscience affords knowledge that can be leveraged in the ontological valuation of individuals, groups, and species. Sociocultural sentiments, norms, and mores may impede embracing such knowledge to revise moral attitudes, ethics, and policies. We argue that the practices of neuroethics will be valuable in that they ground ethico-legal discourse in (1) naturalistic philosophy; (2) the current epistemological capital of neuroscience; (3) the issues, problems, and solutions arising in and from neuroscientific research and its applications; and 4) the use of neurocentric criteria—such as painience—to define and resolve ethical decisions regarding attitudes toward and treatment of nonhuman animals.